A comparative analysis of endoscopic sinus surgery versus biologics for treatment of chronic rhinosinusitis with nasal polyposis. Issue 2 (4th September 2022) - Miglani, Amar; Soler, Zachary M.; Smith, Timothy L.; Mace, Jess C; Schlosser, Rodney J.
Abstract: Background: Comparative effectiveness research between endoscopic sinus surgery (ESS) and biologic therapy for severe chronic rhinosinusitis with nasal polyposis (CRSwNP) is a nascent field as new therapeutic modalities become clinically available. Methods: A prospective, multicenter cohort of CRSwNP patients, undergoing ESS between 2011 and 2019, were compared to phase‐3 biologic trial data. Patients undergoing ESS received baseline nasal endoscopy quantified via Lund‐Kennedy (LK) grading. Patients meeting inclusion criteria, modified from Dupilumab‐LIBERTY‐NP‐24&52, omalizumab‐POLYP‐1&2, and Mepolizumab‐SYNAPSE clinical trials, were included in this study. Baseline characteristics and outcome measures were compared between these cohorts at 24 weeks and 52 weeks, when possible. Results: A total of 111 CRSwNP patients met modified inclusion criteria. There were no statistically significant differences in baseline age, sex, asthma status, aspirin‐exacerbated respiratory disease status, smell identification, LK‐polyp score, and Lund‐Mackay computed tomography (CT) scores between ESS and biologic groups. At 24 weeks, ESS demonstrated significantly greater improvements in 22‐item Sino‐Nasal Outcome Test (SNOT‐22) compared to one (of two) dupilumab trials ( p  < 0.05) and both omalizumab trials ( p  < 0.001). ESS associated with significantly lower nasal polyp scores (NPS) compared to dupilumab ( p  < 0.001) and omalizumab ( p  < 0.001), despite comparable improvements in smell identification ( p  > 0.05). At 52 weeks, ESS resulted in statistically similar improvement in SNOT‐22 scores compared to dupilumab ( p  = 0.21), but NPS remained significantly lower in the ESS group compared to dupilumab ( p  < 0.001) and mepolizumab ( p  < 0.001). Conclusion: At 24 weeks and 52 weeks, ESS offers comparable SNOT‐22 improvements compared to dupilumab. ESS and dupilumab offer comparable improvement in smell identification at 24 weeks. Compared to omalizumab, ESS offers superior SNOT‐22 improvements. ESS offers significantly greater reductions in polyp size compared to omalizumab, dupilumab, and mepolizumab therapies.